Technology Integration in English Language Teaching : Analysis of Teachers' Perceptions and Practices in the Digital Era - Andi Suwarni; Nurasia Natsir (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research investigates English language teachers' perceptions and practices concerning technology integration within the Indonesian educational landscape. Employing a mixed-methods approach, the study involved 120 English teachers from diverse educational levels, including primary, junior high, senior high, and higher education institutions. Participants completed an online survey, and a subset of 15 teachers was selected for follow-up interviews and classroom observations to provide deeper qualitative insights. The findings indicate a significant discrepancy between teachers’ generally positive attitudes toward the use of technology (mean score = 4.21 on a 5-point Likert scale) and the extent to which they actually implement technology in their teaching practices (mean score = 3.15). This gap suggests that favorable perceptions alone are not sufficient to ensure effective classroom integration. Through statistical analysis, four primary factors were identified as influencing technology integration. These include teachers’ digital competence (β = 0.43, p < 0.01), institutional support (β = 0.38, p < 0.01), pedagogical beliefs (β = 0.35, p < 0.01), and access to adequate infrastructure (β = 0.32, p < 0.01). These results highlight the multifaceted nature of technology integration, where both individual competencies and systemic support play crucial roles. Qualitative data further enrich the findings by illustrating the lived experiences of teachers. While educators recognize that technology can enhance student engagement, foster interactive and authentic language learning environments, and provide access to diverse resources, they encounter several challenges. These include difficulties in aligning digital tools with curricular goals, managing student behavior in tech-enhanced classrooms, and assessing learning outcomes effectively in digital contexts.